Research Note: Association of VIPR-1 gene polymorphism with growth traits in meat type Japanese quail (Coturnix Japonica) - Bai, Junyan; Wang, Xinle; Li, Jingyun; Chen, Mengke; Zeng, Fanlin; Lu, Xiaoning; He, Yuhan (Poultry science, 2023)
This study aimed to analyze the polymorphism of the vasoactive intestinal peptide receptor-1 (VIPR-1) gene and its association with growth traits in quail using the PCR-RFLP and sequencing techniques. Genomic DNA was extracted from blood samples of 36 female Savimalt (SV) quails and 49 female French Giant (FG) quails. Growth traits were measured and used for VIPR-1 gene analysis, as body weight (BW), tibia length (TL), chest width (CW), chest depth (CD), sternum length (SL), body length (BL), and tibia circumference (TC). The results showed that 2 SNPs (BsrD I and HpyCH4 IV) were detected in exon 4 to 5 and exon 6 to 7 of the VIPR-1 gene, respectively. The results of association showed that the BsrD I site was not significantly associated with growth traits at 3 or 5 wk of age in the SV strain (P < 0.05), while the BsrD I site was significantly associated with BL at 3 or 5 wk of age in FG (P < 0.05). The HpyCH4 IV site was significantly associated with TL, CW, CD, SL, and BL at 3 wk of age in the SV strain (P < 0.05), while the HpyCH4 IV site was significantly correlated with BW, CW, SL, and BL at 5 wk of age in SV (P < 0.05). The HpyCH4 IV site was significantly associated with TL and TC at 3 wk of age in FG (P < 0.05), while the HpyCH4 IV site was significantly associated with TC at 5 wk of age in FG (P < 0.05). Four haplotype combinations based on 2 SNPs showed significantly association with BW, CW, CD, SL, BL, and TC at 3 or 5 wk of age in SV (P < 0.05). There was not significant association between 3 haplotype combinations with growth trait at 3 or 5 wk of age in FG (P > 0.05). In conclusion, the VIPR-1 gene could be used as a molecular genetic marker to improve growth traits in quail.